The role of small extracellular vesicles in post-traumatic stress disorder - Haixin Zhang; Qile Zhang; Shicheng Li; Fanzhen Kong (Global Medical Genetics)
Post-Traumatic Stress Disorder (PTSD) represents a significant mental health challenge closely associated with the consequences of traumatic experiences. Recently, small extracellular vesicles (sEVs) have been recognized as vital elements in the facilitation of intercellular communication. This review delves into the potential roles and mechanisms of sEVs in PTSD, concentrating on their involvement in neural signaling, immune system reactions, and the modulation of molecular biomarkers related to psychological disorders. By integrating recent research outcomes, this article aims to provide fresh insights into the pathophysiological aspects of PTSD and investigate prospective therapeutic approaches, underlining the significance of sEVs within the broader context of stress-related conditions.